Características clínicas, epidemiológicas y electroneuromiográficas de los pacientes con diagnóstico de Síndrome de Guillain Barré - Sánchez Quispe, María Leandra (2019)
Describe the clinical, epidemiological and electroneuromyographic characteristics of patients with a diagnosis of Guillain Barré Syndrome. Material and method: Retrospective, descriptive, observational study. All the medical records of the patients with a diagnosis of Guillain Barré Syndrome treated at the Trujillo Regional Teaching Hospital during 2018 were reviewed. The medical records with complete data of hospitalized patients with a diagnosis of Guillain Barré Syndrome are included. at the Trujillo Regional Teaching Hospital during 2018. Were excluded: medical records of patients diagnosed with botulism, myasthenia, poliomyelitis or toxic neuropathy; Medical histories of patients with a diagnostic history of inflammatory polyneuropathy: Medical records with incomplete data of patients diagnosed with Guillain Barré Syndrome. Epidemiological, clinical and electromioneurographic variables were used. A data collection form was formulated with the variables of interest to meet the objective of the study. The registration of data consigned in the corresponding data collection sheets was carried out in a database created with the Microsoft Excel 2013 program, which was then processed using the SPSS 23.0 statistical package and presented in tables and in relevant graphs based on measures of central tendency (mean and standard deviation) for the case of quantitative variables and as absolute and relative percentage frequencies for qualitative variables. The study was authorized by the Research and Ethics Committee of the Trujillo Regional Teaching Hospital and the National University of Trujillo. Likewise, the declaration of Helsinski II (Numerals: 11,12, 14, 15, 22,23) and the General Health Law No. 268420 (Title IV: Art. 117 and 120) of the School's Code of Ethics and Deontology were considered. Doctor of Peru, respecting the principles of autonomy and justice of the Belmont Report.